Release from the Pressure of the EU Competition Law - Deák, Dániel (Challenges of Contemporary Tax Law: Jubilee Book Dedicated to Professor Włodzimierz Nykiel. Volume II, 2024)
What follows is to share some thoughts on how the Member States’ tax law has developed and may develop in the future in an EU environment where special sectoral taxes are accepted. Tax law considerations are increasingly subordinated to the interests of the freedom of global capital markets. Flexibility is needed in changing market conditions, but such a development makes it difficult to enforce legal certainty, which is a crucial feature of tax law. The resilience of regulators is meaningful in economics, but it can hardly be coordinated with a legal system’s stability. Concerning progressive taxes on turnover, for the time being, defenders of nation-state sovereignty seem to gain against those who want to open European capital markets and further harmonise the relevant regulations to remove administrative barriers from the freedom of capital. However, the future tells us how much national tax law systems can preserve their cohesion in the EU, an integral part of the global economy.